Patterns of Hepatitis C Virus RNA Levels during Acute Infection: The InC(3) Study - Hajarizadeh, Behzad (PLoS One, 2015)
BACKGROUND: Understanding the patterns of HCV RNA levels during acute hepatitis C virus (HCV) infection provides insights into immunopathogenesis and is important for vaccine design. This study evaluated patterns of HCV RNA levels and associated factors among individuals with acute infection. METHODS: Data were from an international collaboration of nine prospective cohorts of acute HCV (InC(3) Study). Participants with well-characterized acute HCV infection (detected within three months post-infection and interval between the peak and subsequent HCV RNA levels≤120 days) were categorised by a priori-defined patterns of HCV RNA levels: i) spontaneous clearance, ii) partial viral control with persistence (≥1 log IU/mL decline in HCV RNA levels following peak) and iii) viral plateau with persistence (increase or <1 log IU/mL decline in HCV RNA levels following peak). Factors associated with HCV RNA patterns were assessed using multinomial logistic regression. RESULTS: Among 643 individuals with acute HCV, 162 with well-characterized acute HCV were identified: spontaneous clearance (32%), partial viral control with persistence (27%), and viral plateau with persistence (41%). HCV RNA levels reached a high viraemic phase within two months following infection, with higher levels in the spontaneous clearance and partial viral control groups, compared to the viral plateau group (median: 6.0, 6.2, 5.3 log IU/mL, respectively; P=0.018). In the two groups with persistence, Interferon lambda 3 (IFNL3) CC genotype was independently associated with partial viral control compared to viral plateau (adjusted odds ratio [AOR]: 2.75; 95%CI: 1.08, 7.02). In the two groups with viral control, female sex was independently associated with spontaneous clearance compared to partial viral control (AOR: 2.86; 95%CI: 1.04, 7.83). CONCLUSIONS: Among individuals with acute HCV, a spectrum of HCV RNA patterns is evident. IFNL3 CC genotype is associated with initial viral control, while female sex is associated with ultimate spontaneous clearance.